Guía psicoeducativa grupal para afrontar los estresores académicos de los estudiantes de primer año de bachillerato paralelo a, de la unidad educativa Marieta de Veintimilla, 2018-2019. - Jaramillo Sojos, Josue Francisco (2019)
The main objective of this degree work was to implement a group psychoeducational guide to address the academic stressors of the first-year students of parallel Baccalaureate A, of the Marieta de Veintimilla Educational Unit. The research was a descriptive, quasi-experimental and cross-sectional study, the scientific, deductive, inductive, analytical, synthetic, and statistical methods were used, the SISCO Academic Stress Inventory was applied, in a sample of 28 students in ages 14 to 16 years. The initial results (pre-test) showed that the students mostly maintain a deep level of academic stress with 71.43%; followed by the moderate level with 21.43% and a low mild level of stress of 14.28%, the academic stressors most frequently found are for 71.43% is the competition between groupmates, for 60.71% the stressor is the task overload, in the same way with the same percentage is the stressor to the teacher evaluations (exams) and, finally for 57.14% they indicate to the stressor the limited time to do a job. Among the situations that cause them less stress is: the personality and character of the teacher, the type of work that teachers ask, understand and participate in classes. After the intervention, and as a final diagnosis (post-test): the students were located in mild levels of stress, in the following stressors: competition between groupmates (89.28%) and the same percentage for the overload of Homework and limited time to do a job, finally, in the stressor of teacher evaluations (92.86%). Concluding that the group psychoeducational guide is valid to face the academic stressors verified by the Pearson statistical test, reached average positive correlation values.